The Analogy Retriever – an idea generation tool - Han,J; Shi,F; Chen,L; Childs,PRN (Design Society, 2017)
Idea generation plays a vital role in design, but coming up with ideas, especially creative ideas, is often challenging. Analogy is considered as a fundamental component of creativity and a beneficial method for idea generation. This paper presents a computer-based tool, named the Analogy Retriever, for assisting designers in idea generation and prospectively in idea elaboration. The tool is based on an algorithm simulating aspects of the human cognitive process of analogy. It is focused on solving proportional analogy problems (A:B::C:X) by retrieving the unknown term X from a knowledge database. The Analogy Retriever has been indicated to be useful and effective for helping the designers concerned generate creative ideas through conducting a case study. The results indicate that the Analogy Retriever, in its current formulation, can significantly improve the quantity, quality, novelty, and variety of the ideas produced. The tool is suggested to be greatly beneficial to design space exploration and expansion.